2(2y+1)=(5y-2)

Simple and best practice solution for 2(2y+1)=(5y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2y+1)=(5y-2) equation:


Simplifying
2(2y + 1) = (5y + -2)

Reorder the terms:
2(1 + 2y) = (5y + -2)
(1 * 2 + 2y * 2) = (5y + -2)
(2 + 4y) = (5y + -2)

Reorder the terms:
2 + 4y = (-2 + 5y)

Remove parenthesis around (-2 + 5y)
2 + 4y = -2 + 5y

Solving
2 + 4y = -2 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
2 + 4y + -5y = -2 + 5y + -5y

Combine like terms: 4y + -5y = -1y
2 + -1y = -2 + 5y + -5y

Combine like terms: 5y + -5y = 0
2 + -1y = -2 + 0
2 + -1y = -2

Add '-2' to each side of the equation.
2 + -2 + -1y = -2 + -2

Combine like terms: 2 + -2 = 0
0 + -1y = -2 + -2
-1y = -2 + -2

Combine like terms: -2 + -2 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx | | 12z+4x=-7 | | 27q-9=180 | | 112x^2-56x=0 | | 2y-7=5-y | | x+.7y=238 | | z=2+3i | | 6n+3+15n+48+3n+10= | | 16r^2-121=0 | | 2/7x7/1 | | 4=(1/4)ax | | 9v-2+2(2v+9)=-2(v+1) | | 12=2x^2-x | | 2[4x-3]=0 |

Equations solver categories